2015
DOI: 10.1007/s12098-015-1734-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Umbilical Cord Milking and Delayed Cord Clamping on Cerebral Blood Flow in Term Neonates

Abstract: DCC and UCM had similar effect on cerebral blood flow velocities and Doppler indices in MCA, in term neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 18 publications
2
28
1
1
Order By: Relevance
“…This might explain higher mean Hb level in UCM group in trial carried out by Rabe et al 24 A similar trial from our institute also reported that Hb and hematocrit in initial 48 h were similar in UCM and DCC groups in full-term infants. 26 Ceriani et al 31 demonstrated that 3 min of DCC in term infants improved serum ferritin level at 6 months of age without any significant change in mean Hb level, which was similar to our primary outcome at 6 weeks of age in DCC group. However, this effect of DCC did not last till 12 months of age as demonstrated by Andersson et al 32 in 382 full-term infants that iron status and neurodevelopmental outcomes were similar in DCC (⩾180 s) and early cord clamping group (⩽10 s).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This might explain higher mean Hb level in UCM group in trial carried out by Rabe et al 24 A similar trial from our institute also reported that Hb and hematocrit in initial 48 h were similar in UCM and DCC groups in full-term infants. 26 Ceriani et al 31 demonstrated that 3 min of DCC in term infants improved serum ferritin level at 6 months of age without any significant change in mean Hb level, which was similar to our primary outcome at 6 weeks of age in DCC group. However, this effect of DCC did not last till 12 months of age as demonstrated by Andersson et al 32 in 382 full-term infants that iron status and neurodevelopmental outcomes were similar in DCC (⩾180 s) and early cord clamping group (⩽10 s).…”
Section: Discussionsupporting
confidence: 85%
“…Standard technique of milking the cut cord was demonstrated by online video by William Tarnow Mordi et al 25 Obstetricians were sensitized enough regarding position of the baby in cesarean and vaginal delivery as well as their role during different interventions as they were a part of similar studies at our institute. 23,26 Just after delivery, depending upon random number slips, participants were allocated one of the three intervention groups, that is, milking the cut cord (UCM), DCC and DCC with milking the cut cord (DCM). In UCM group, just after delivery, umbilical cord was clamped and cut immediately (⩽10 s) at placental end leaving cord length of at least 25 cm from the umbilicus of baby.…”
Section: Methodsmentioning
confidence: 99%
“…There was no significant difference in polycythemia, serum bilirubin, and need of phototherapy between groups. Jaiswal et al compared C-UCM to DCC of 60–90 s (100 in each group) in babies born >36 weeks gestational age (55). Mean serum ferritin at 6 weeks of age in the C-UCM group (134.0 ± 89.8 ng/ml) was comparable to DCC (142.7 ± 87.1 ng/ml).…”
Section: Methods Of Providing a Placental Transfusionmentioning
confidence: 99%
“…Este procedimiento puede tener efectos similares al pinzamiento tardío del cordón umbilical en prevención de anemia, reducción de hemorragia intraventricular, sepsis, enterocolitis necrosante, retinopatía del prematuro y displasia broncopulmonar. [10][11][12][13][14] A diferencia del pinzamiento tardío, el ordeño del cordón no retrasa el proceso de reanimación neonatal, sobre todo en prematuros críticamente enfermos, lo que puede constituir una ventaja para este procedimiento. 15 El pinzamiento temprano del cordón umbilical; es decir, antes de los 30 segundos de vida, aún es una práctica habitual en nuestro medio asociada con una serie de complicaciones en el recién nacido, incluida la mayor frecuencia de anemia.…”
Section: Discussionunclassified